Integrating proteomics and enzymatic profiling to decipher seed metabolism affected by temperature in seed dormancy and germination. (April 2018) - Xia, Qiong; Ponnaiah, Maharajah; Cueff, Gwendal; Rajjou, Loïc; Prodhomme, Duyen; Gibon, Yves; Bailly, Christophe; Corbineau, Françoise; Meimoun, Patrice; El-Maarouf-Bouteau, Hayat
Highlights: Proteome characterization in temperature-induced seed germination showed the importance of metabolism and energy components. Metabolism related enzyme activities were lowered in germinating compared to non-germinating seeds at the phase I of germination sensu stricto . The regulation of central metabolism activity is important in the control of germination. Abstract: Temperature is an important environmental factor affecting seed dormancy and germination. The mechanism by which temperature induces germination in dormant seeds is however still unclear. Proteomic study has been performed in dormant sunflower seeds during imbibition at permissive and non-permissive temperatures for germination, 20 and 10 °C, respectively. Proteome analysis showed an increase of proteins belonging to metabolism and energy from the first hours of imbibition followed by a decrease of proteins involved in protein metabolism and seed storage in germinating compared to non-germinating seeds. Proteomic study was completed by polysome and proteasome activity assessment and enzymatic profiling on several altered proteins involved in metabolism and energy. Results showed that 20 °C treatment induced the activation of both protein synthesis and degradation processes, the latter being related to proteasome activity during the germination sensu stricto, and to other degradation processes such as proteases during the post-germination. Interestingly, enzymatic profiles showed that TCA cycle and glycolysis were more active in non-germinating seeds in the phase I of the germination sensu stricto . This result suggests the regulation of central metabolism activity in germinating seeds. The control of energy production during imbibition seems to be involved in molecular networks controlling seed dormancy and germination.